KIR AA individuals possess strong inhibitory KIR alleles alongside HLA ligands that are protective against leukemia in the Chinese population - Deng, Zhihui; Zhen, Jianxin; Li, Yunan; Liang, Shuang; Zhang, Manru; Cai, Siqi; Jiang, Renhui; Yang, Zhichao; Yu, Qiong; Wang, Jinyong; Liu, Jie (Frontiers in Genetics, 2026)
IntroductionThe killer-cell immunoglobulin-like receptor (KIR) gene cluster exhibits complicated diversity in haplotype content, copy-number variation (CNV), and allelic polymorphism. To date, 2,286 distinct KIR alleles have been released in the IPD-KIR Database. However, little is known about the impact of high-resolution-level KIR allelic polymorphisms on leukemia. Our previous study showed that the KIR AA genotype carrying more inhibitory genes conferred differential protection against leukemia in the Chinese Southern Han population. Herein, we hypothesized the impact of KIR alleles in the KIR A haplotype and cognate human leukocyte antigen (HLA) ligand on leukemia.MethodsThe study cohort included 318 ALL patients, 336 AML patients, and 306 unrelated healthy controls. All the study samples were subject to HLA-A, -B, and -C sequencing-based genotyping (PCR-SBT) and high-resolution KIR genotyping for all the seven functional KIR genes (KIR2DL1, KIR2DL3, KIR2DL4, KIR3DL1, KIR3DL2, KIR3DL3, and KIR2DS4) on the KIR A haplotype. HLA and KIR genotypes were assigned using Assign 4.7.1 software.ResultsIn the present study, our high-resolution genetic analysis revealed protective KIR–HLA interactions in individuals with the KIR AA genotype. The strong inhibitory KIR2DL1*00201+C2 interaction reduced ALL risk (p = 0.01), while KIR2DL1*00302 +C2 (p = 0.008), KIR2DL3*00201+C1 (p = 0.03), and KIR3DL1*00501+Bw4 80I (p = 0.008) interactions protected against AML (p < 0.05). However, the functionally weaker inhibitory KIR2DL1*004+C2 interaction conferred ALL risk (p = 0.01) in individuals with the KIR Bx genotype. Notably, we found that the allelic polymorphisms of the structure gene KIR3DL3 were associated with the occurrence of leukemia. KIR3DL3*001 tends to confer protection against AML (8.4% vs. 1.3%, p = 0.004, Pc = 0.06), whereas KIR3DL3*009 conferred susceptibility to AML (29.3% vs. 47.1%, p = 0.001, Pc = 0.016). KIR3DL3*001 differs from KIR3DL3*009 by an amino acid substitution of non-charged asparagine (N) to charged histidine (H) in its transmembrane domain, suggesting that this functional variant site KIR3DL3_N300H may play a critical role in the occurrence of leukemia in the Chinese population.ConclusionThese data suggest that KIR AA individuals possess strong inhibitory interactions of KIR alleles and HLA, arming KIR AA+ NK cells to meditate stronger alloreactivity and cytotoxicity against leukemia cells with lowered HLA expression. Our findings may provide valuable insights into leukemia pathogenesis and better understanding of the immune mechanisms.